2014
DOI: 10.5007/1980-0037.2014v16n3p277
|View full text |Cite
|
Sign up to set email alerts
|

Perfil morfológico, maturacional, funcional e técnico de jovens futebolistas Brasileiro

Abstract: -The objectives of this study were to describe and compare the anthropometric profile, physical fitness and soccer-specific skills between under-15 and under-17 Brazilian soccer players, as well as to evaluate possible differences in these variables according to biological maturation in the age categories. The sample consisted of 245 male soccer players (under-15: n=161; under-17: n=84). Anthropometric measures included weight, height and skinfolds. Biological maturation was assessed based on pubic hair develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 20 publications
2
5
0
Order By: Relevance
“…Apart from its prognostic validity, the higher reliability (r tt = .79) compared to other SMP tests in the current study (.31 ≤ r tt ≤ .68), and the substantial factor loading on the latent dimension technical skills, may be hints for the high value of juggling (Höner et al, 2015). Earlier results on its independence from biological maturation are confirmed in the current study, albeit this is also true for the other three SMP tests (Figueiredo, Goncalves, Silva, & Malina, 2009b;Matta, Figueiredo, Garcia, & Seabra, 2014). Following these results, the use of juggling tests within talent selection in youth football is highly recommended.…”
Section: Prognostic Validity and Time Spansupporting
confidence: 73%
“…Apart from its prognostic validity, the higher reliability (r tt = .79) compared to other SMP tests in the current study (.31 ≤ r tt ≤ .68), and the substantial factor loading on the latent dimension technical skills, may be hints for the high value of juggling (Höner et al, 2015). Earlier results on its independence from biological maturation are confirmed in the current study, albeit this is also true for the other three SMP tests (Figueiredo, Goncalves, Silva, & Malina, 2009b;Matta, Figueiredo, Garcia, & Seabra, 2014). Following these results, the use of juggling tests within talent selection in youth football is highly recommended.…”
Section: Prognostic Validity and Time Spansupporting
confidence: 73%
“…It has been revealed that the mean body height, body weight, body mass index, skeletal muscle mass, percentage of body fat mass, fat-free mass, total body water and basal metabolic rate of the U-15 soccer players was significantly lower than in the remaining groups of soccer players, U-17, U-19, and seniors. The larger body size for U-17 compared to U-15 soccer players was also confirmed by Da Silva et al's, and Matta et al's research [16,18]. Lower total body water and basal metabolic rate in the younger competitive age-related category were also previously found in [19].…”
Section: Discussionsupporting
confidence: 73%
“…Small body composition differences between the aforementioned competitive age-related soccer categories may have not been significant. Meanwhile, in the U-15 group, the impact of biological development is the greatest compared to the remaining competitive age ranks [18], which could have influenced inconsistent, non-linear changes in morphological characteristics across agerelated soccer groups. In addition, the possible reason for failure to differentiate seniors' body composition from the body composition of U-17 and U-19 could be the smaller sample size and wider age range of senior soccer players relative to the U-17 and U-19 groups.…”
Section: Discussionmentioning
confidence: 99%
“…Computation of YYIE2 test global means, SDs and quantiles (Figure 4) included 48 studies/subgroups and 1,466 participants (median age = 23.0 years, IQR = 18.3–26.0 years) (Aziz et al, 2005; Rampinini et al, 2007; Bangsbo et al, 2010; Brito et al, 2010; Krustrup et al, 2010a,b,c, 2015; Randers et al, 2010, 2013; Ascensão et al, 2011; Bradley et al, 2011, 2013, 2014; Rebelo et al, 2011, 2013; Silva et al, 2011, 2013; Gibson et al, 2013; Dixon, 2014; Massuça et al, 2014; Massuca et al, 2015; Matta et al, 2014; Póvoas et al, 2014; Kvorning et al, 2017). …”
Section: Resultsmentioning
confidence: 99%